Research on High-Quality Development Models of The Grain Industry Under the New Development Concept - Wen, Wu (Transactions on Economics, Business and Management Research, 2024)
Ensuring food security is fundamental to national stability, and agricultural stability is key to societal well-being. Under the guidance of the new development concept in this new era, the high-quality development of the grain industry has become a central goal for securing national food security, advancing agricultural modernization, and achieving sustainable development. This study aims to systematically review the existing literature, clarify the current state and primary challenges of high-quality development in the grain industry, and summarize and analyze the foundation of China’s high-quality grain industry development model. Furthermore, it focuses on potential innovative models for high-quality development under the new development concept. This review offers a comprehensive perspective and strong support for the theoretical construction and practical innovation of the grain industry’s high-quality development model. Additionally, the research findings will provide valuable references for future strategies and policy-making in the grain industry, assisting governments and relevant sectors in better understanding how to achieve the dual objectives of food security and sustainable development through innovation and coordinated growth.